TECHNOLOGY-MEDIATED TASK-BASED LEARNING (TTL) TO IMPROVE STUDENT’S PRODUCTIVE SKILLS IN PRIMARY SCHOOL - Ahmad Haerudin, Dodi; Falah, Irfan Fajrul; Kusumah, Rita (STKIP Siliwangi, 2024)
English language skills, especially speaking and writing, are essential since it can help the students to express their ideas and thoughts. However, developing these skills takes work and require serious effort. The combination of technology and technology-mediated task-based learning (TBLT) is a suitable formula to improve speaking and writing skills, especially for students in elementary schools. This is a mixed-method study where qualitative and quantitative approaches complement each other. A total of 56 4th-grade elementary school students who were divided into experimental groups (n-28) and control groups (n-28) became participants in this study. The data collection techniques used were tests, observation, and interviews. Meanwhile, for data analysis, this study used statistical analysis for quantitative data and content analysis for qualitative data. The results indicate that the use of technology-mediated task-based learning had an effect on students' speaking and writing skills. This can be seen from the statistical test results of Asymp. Sig two-tailed (0.037) that is lower than 0.05. In addition, using Technology-mediated task-based learning has several advantages, including creating exciting learning and increasing students' engagement. However, several challenges must also be considered, including teacher creativity in designing and the need for students to adapt to the implemented design.